STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN BERBASIS POTENSI LOKAL DI PULAU TILAN DENGAN PENDEKATAN ANALISIS SWOT - Jingga Lestari; Andri Wibowo; Arina Luthfini Lubis (Bajang Institute, 2025)
This study aims to analyze sustainable tourism development strategies based on local potential in Pulau Tilan, Rokan Hilir Regency, Riau Province using the SWOT analysis approach. Data were collected through observation, interviews, and documentation. The results show that Pulau Tilan has strong natural and cultural potential as main strengths, but tourism development is hindered by limited infrastructure, community participation, and suboptimal management. The SWOT analysis divides development strategies into four categories to optimize strengths and opportunities while addressing weaknesses and threats. This study provides strategic recommendations to support sustainable tourism development in Pulau Tilan based on local community involvement. The findings are expected to serve as a guideline for policymakers and destination managers to ensure successful sustainable tourism management.